Preparation of vitamin B12–TiO2 nanohybrid studied by TEM, FTIR and optical analysis techniques. (July 2015) - Gharagozlou, Mehrnaz; Naghibi, Sanaz
Abstract: Vitamin B12 (VB12 ) was applied to modify TiO2 nanoparticles (NPs) for the first time. TiO2 NPs were synthesized via sol–gel method. In the next step, as-synthesized NPs were modified by VB12 . Fourier transform infrared (FTIR) spectroscopy demonstrated the formation of primary bonds between NPs and VB12 . Thermogravimetric analysis (TGA) was also utilized to calculate the proportion of NPs to VB12 . The percentage of VB12 gained was ~20 wt%. The band gap value decreased from 3.27 (TiO2 ) to 3.20 eV and the photocatalytic degradation of Rhodamine B (RB) solution diluted in VB12 –TiO2 NPs. The photoluminescence (PL) intensity increased from 3 to 6 cd. This is because the total pore volume raised about 18% by modifying TiO2 NPs; therefore, the photogenerated charge-carrier recombination rate increases by the VB12 loading.